Human Resource Investment Strategy in Increasing Productivity of Economic Sectors in Indonesia: Penelitian - Syamsu Rijal; Andi Caezar To Tadampali; Marhawati; Nur Arisah; Sri Hutami Adiningsih S (Lembaga Penelitian dan Pengabdian Masyarakat, 2025)
This study aims to describe the human resource (HR) investment strategy and its impact on the productivity of the economic sector in Indonesia, as well as to identify challenges and gaps in its implementation. The research method used is descriptive qualitative with secondary data analysis from various official sources such as the Central Statistics Agency, related ministries, and international institutions. The results of the study indicate that the HR investment strategy in Indonesia includes the development of formal education, vocational training, increasing digital competence, and improving health services. The positive impact is reflected in the increase in the Human Development Index (HDI), labor productivity in the industrial and service sectors, and better national competitiveness. However, there are a number of challenges, including inequality of access between regions, mismatch of competence with industry needs, limited role of the private sector, and policy fragmentation. This study recommends increasing equal access, strengthening partnerships between education and industry, optimizing the role of the private sector, and integrating data-based systems and governance to increase the effectiveness of HR investment in Indonesia. These findings are expected to be a reference for policy makers in designing more inclusive and productive HR development policies.